EFEKTIVITAS PRAKTIK KEPENDIDIKAN UNTUK MENINGKATKAN EFISIENSI DIRI MENGAJAR PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS - Susilowati, Nenden (Jurnal Ekonomi dan Pendidikan, 2023)
Economics subjects are still considered difficult by most, and this is a challenge for teachers to be able to teach economics well. Therefore, prospective teachers need to have self-efficacy in their ability to teach economics material. This study aims to determine the effectiveness of educational practices to improve teaching self-efficacy in 21 students majoring in Education in the VII Semester of the Faculty of Economics. This study uses an experimental method with a one-group pretest-posttest design. The teaching self-efficacy variable was measured using the Teaching Self-Efficacy Scale, which was tested on 115 students in the seventh semester of the Faculty of Economics, with the result of Cronbach's alpha reliability coefficient of 0.86. The results of this study indicate a significant increase in the average teaching self-efficacy score of 14.45%, with a significance value of 0.003 (p < 0.05). Follow-up analysis of aspects of teaching self-efficacy showed that the magnitude score increased by 21.73% (sig=0.003; p¡0.005), and generality increased by 22.37% (sig=0.002; p¡0.005), and strength increased by 25.58. % (sig=0.003; p¡0.005). Thus, it can be concluded that educational Practice can significantly improve teaching self-efficacy for students majoring in Education at the Faculty of Economics and Business.